Attitudes of electronic cigarette users towards electronic cigarette and their usage habits - Dayi, Ali; Kahraman, Süleyman; Korkut, Selim Erçin (Journal of Dependence, 2019)
Objective: The aim of this study is to evaluate attitudes of electronic cigarette (e-cigarette) users towards e-cigarette and their e-cigarette usage habits.Method: The data collected from 269 e-cigarette users from a social media forum. In order to collect data online versions of a questionnaire developed by the researchers was used.Results: Results revealed that 97% of the participants were using conventional cigarette before e-cigarette use, 62,8% of them began to use e-cigarette to quit conventional cigarette, 34.2% of them were still using conventional cigarette with e-cigarette, 61.7% of them were using e-cigarette more than 12 months, 51.7% of them were using e-cigarette in within 30 minutes after they woke up and 100% of the recommended e-cigarette to conventional cigarette users.Conclusion: This study points out the attitudes of e-cigarette users towards e-cigarette and their usage habits. Positive attitudes of participants towards e-cigarette usage contribute nicotine addiction. Doing more researches about long term effects of e-cigarette usage on human health becomes more important for public health.
Keywords: Electronic cigarette; nicotine; smoking